The burden of eating disorder risk in Chinese adolescents: prevalence, multilevel correlates, and psychosocial differences in a national study - Jiamin Bao; Pinky Gan; Junkai Feng; Yixuan Wang; Yanfeng Luo; Yinyin Zang (BMC Medicine)
Abstract Background Eating disorders (EDs) are a growing health concern among children and adolescents globally, yet their prevalence and associated factors in China remain underexplored. This study aimed to update epidemiological data on screening-detected EDs and to examine multilevel associated factors in a large, representative sample of Chinese adolescents. Methods Cross-sectional data were drawn from the 2021–2022 Child to Adult Mental and Physical Health Study (CAMPS). Using a geographically stratified sampling approach with sample weights calibrated to 2020 Census demographics, we recruited 41,406 adolescents aged 10–19 across eastern, central, and western China. Probable EDs were assessed using the SCOFF questionnaire, with clinical significance evaluated through anxiety and depression scales. Psychosocial functioning was compared between adolescents with and without probable EDs. Associated factors spanning individual, family, and regional levels were examined using multivariate logistic regression. Results The prevalence of probable EDs was 21.18% (95% CI: 20.33–22.04), decreasing to 11.33% (95% CI: 10.68–11.99) when considering clinical significance. Adolescents with probable EDs exhibited significantly poorer psychosocial functioning compared to their peers, including lower academic engagement and higher self-harm, externalizing behaviors, and suicide risk (Cohen’s ds ≥ 0.28, ps < 0.001). Being female (OR = 1.88, 95% CI: 1.32–2.68, p < 0.001), having higher BMI (OR = 1.02, 95% CI: 1.01–1.03, p < 0.001), increased mobile phone use (OR = 1.06, 95% CI: 1.05–1.07, p < 0.001), lower familial subjective socioeconomic status (SES) (OR = 0.92, 95% CI: 0.89–0.96, p < 0.001), lower subjective SES in school (OR = 0.91, 95% CI: 0.87–0.95, p < 0.001), and living in less developed regions (OR = 0.23, 95% CI: 0.08–0.70, p = 0.010) were significantly associated with increased risk of probable EDs. Cohabitating with the father (ORs = 0.65 to 0.77, ps < 0.033) was protective in some provinces. Conclusions This study reveals a substantial burden of probable EDs among Chinese adolescents, with weighted prevalence rates comparable to global estimates and markedly higher than a decade ago. These findings underscore the importance of prioritizing EDs as a public health concern in China and advocate for targeted, multilevel interventions that address both individual and socio-ecological associated factors.